2014
DOI: 10.1016/j.pocean.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Coupled wind-forced controls of the Bering–Chukchi shelf circulation and the Bering Strait throughflow: Ekman transport, continental shelf waves, and variations of the Pacific–Arctic sea surface height gradient

Abstract: Available online xxxx a b s t r a c tWe develop a conceptual model of the closely co-dependent Bering shelf, Bering Strait, and Chukchi shelf circulation fields by evaluating the effects of wind stress over the North Pacific and western Arctic using atmospheric reanalyses, current meter observations, satellite-based sea surface height (SSH) measurements, hydrographic profiles, and numerical model integrations. This conceptual model suggests Bering Strait transport anomalies are primarily set by the longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
134
2
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 168 publications
(155 citation statements)
references
References 100 publications
(161 reference statements)
18
134
2
1
Order By: Relevance
“…In contrast, a mostly negative AO in the late Holocene can be inferred from mineralogical proxy data indicating a general decline in the BSI after 4 ka ), which could be attributed to a stronger Aleutian Low (Danielson et al, 2014) that typically corresponds to the negative AO (Overland et al, 1999). Olsen et al (2012) also concluded that the AO tended to be mostly negative from 4.2 to 2.0 ka based on a redox proxy record from a Greenland lake.…”
Section: Holocene Trend In the Beaufort Gyre Circulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, a mostly negative AO in the late Holocene can be inferred from mineralogical proxy data indicating a general decline in the BSI after 4 ka ), which could be attributed to a stronger Aleutian Low (Danielson et al, 2014) that typically corresponds to the negative AO (Overland et al, 1999). Olsen et al (2012) also concluded that the AO tended to be mostly negative from 4.2 to 2.0 ka based on a redox proxy record from a Greenland lake.…”
Section: Holocene Trend In the Beaufort Gyre Circulationmentioning
confidence: 99%
“…Recently, a conceptual model of the BSI controls has been developed based on a decade of oceanographic observations (Danielson et al, 2014). According to this model, storms centered over the Bering Sea excite continental shelf waves on the eastern Bering shelf that intensify the BSI on synoptic timescales, but the integrated effect of these storms tends to decrease the BSI on annual to decadal timescales.…”
Section: Oceanographic Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Pacific sector, frequent low-pressure systems (storms) exert strong control over the western Arctic and sub-Arctic through their influence on ocean circulation patterns, mixing and upwelling (Overland, 1986;Isoguchi et al, 1997;Pickart et al, 2009), and link the two regions through oceanic forcing. For example, these storms mediate flow variations in Bering Strait (e.g., Roach et al, 1995;Cherniawsky et al, 2005;Woodgate et al, 2005b;Danielson et al, 2014) and hence influence the variability of transport of nutrient-rich Pacific waters into the Arctic. Storms that move into the Gulf of Alaska tend to shift the climatological Aleutian Low eastward, reducing transport through Bering Strait over daily to weekly time scales, but cause increased transport anomalies over annual time scales (Danielson et al, 2014).…”
Section: Atmospheric Conditions and Circulation In The Arcticmentioning
confidence: 99%
“…For example, these storms mediate flow variations in Bering Strait (e.g., Roach et al, 1995;Cherniawsky et al, 2005;Woodgate et al, 2005b;Danielson et al, 2014) and hence influence the variability of transport of nutrient-rich Pacific waters into the Arctic. Storms that move into the Gulf of Alaska tend to shift the climatological Aleutian Low eastward, reducing transport through Bering Strait over daily to weekly time scales, but cause increased transport anomalies over annual time scales (Danielson et al, 2014). The annual transport anomalies are associated with a changing Pacific-Arctic sea-level elevation difference that is caused in part by changes in Ekman suction over the deep North Pacific.…”
Section: Atmospheric Conditions and Circulation In The Arcticmentioning
confidence: 99%